Implementasi Manajemen Sarana dan Prasarana Sebagai Penunjang Efektivitas Pembelajaran di Madrasah Aliyah Negeri 1 Pamekasan - Maizah Maizah; Rinta Ratnawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the implementation of facilities and infrastructure management to support the effectiveness of learning at the Aliyah Negeri 1 Pemekasan madrasah. The research method used is a qualitative approach. Data collection was carried out by observation, interviews, and documentation. Based on this research, the results showed that the principal together with the teaching staff at MAN 1 Pamekasan held a meeting regarding planning facilities and infrastructure before the new school year, the principal also asked for input from each person responsible for providing sarpas both in the classroom and outside the classroom, procurement of facilities and Infrastructure is budgeted for BOS funds. Management of facilities and infrastructure at MAN 1 Pamekasan involves four teams, has operational standards (SOP), and uses a record book for borrowing goods. Two factors influence the implementation of facilities and infrastructure management, namely the driving factor for facilities and infrastructure management at MAN 1 Pamekasan is the support and attention from the government to continue building quality facilities for academic smoothness with school operational assistance (BOS), the inhibiting factor is the existence of sarpas are missing or damaged and on the one hand the budget is inadequate. In conclusion, complete facilities and infrastructure support the learning process and even support the achievement of educational goals. Keywords: Facilities and infrastructure management, Learning effectiveness